Socio-Philosophical Analysis of The Formation of An Informed Society in The Context of Globalization - Abdulla Mansurov Sayfullayevich (Scientific Trends, 2023)
This article was given the philosophical assumption that the emergence of an informed society in the context of globalization and is one of its main factors. Conclusions were drawn as a result of a systematic analysis of the conceptual foundations of globalization and an informed society.
Keywords: globalization, information, concept of foreign policy, geopalistics, ideological Polygon, intensification of ideological processes.